An Analysis of Reading Strategies Used by The Fourth Semester Students of English Education Study Program in Muhammadiyah University - Sri Hasibuan; Hilda Puspita; Arasuli Arasuli (Universitas Bengkulu, 2022)
This research aimed at finding out types of reading strategies and the dominant reading strategies used by the fourth semester students of English Education Study Program in Muhammadiyah University. The subject of this research was all fourth semester students of English Education Study Program in academic year 2018/2019. This research used descriptive quantitative method in the form of survey. The data were collected by using the questionnaire as the instrument. The result shows that the fourth semester students of English Education Study Program in Muhammadiyah University used the four reading strategies in reading: cognitive, metacognitive, compensation, and testing strategies. The dominant reading strategy was metacognitive strategy. Among the four strategies, metacognitive strategies (3.2) were the most frequent strategies used by the fourth semester students. It was followed by testing strategies with average score (3.0), compensation strategies with average score (2.9), and finally cognitive strategies with average score (2.8). The four reading strategies were categorized in moderate level. It can be concluded that the students were using the four reading strategies quite well, and they used metacognitive strategy mostly when they do a reading activity in the classroom, such as thinking about the learning process, planning for learning, monitoring the learning task, and evaluating how well one has learned.